A critical analysis of the current TNM classification for differentiated thyroid carcinoma in young patients: Time for a change? - Wang, Wenlong; Bai, Ning; Li, Xinying (Frontiers in Endocrinology, 2022)
Background: The current TNM classification simply classify differentiated thyroid carcinoma (DTC) patients younger than 55 years old into stage Ι and stage II, based on the presence or absence of distant metastases, has been questioned. In this study, we re-examined the impact of T status and N status on prognosis, and then develop a new prediction model to improve the predictability of cancer-specific survival (CSS) in young patients. Materials and methods: Kaplan–Meier method was applied to calculate the CSS. Multivariable Cox proportional hazards models were used to assess the impact of T status and N status on CSS after adjustment for known covariates. The area under receiver-operating characteristic curve (AUC), C-index, Bayesian information criterion (BIC), and Akaike information criterion (AIC) were calculated to compare model performance. Results: Of the total 9242 DTC patients younger than 55 years old were enrolled in the study. After adjusting gender, age at diagnosis, race, pathology subtype, N stage, and M stage, T3 (HR:3.78, P =0.006) and T4 (HR:7.96, P <0.001) disease remain independent predictors of CSS. Similarly, the 10-year CSS rate of N1b disease (HR:3.78, P <0.001) was significantly higher than N0 disease after adjustment. Besides, Kaplan-Meier survival analysis showed that the 10-year CSS of stage Ⅱ disease in younger patients with DTC sharp decrease compared with older patients (74.47% vs.98.43%, P <0.001). Furthermore, a modified TNM staging system based on significantly prognostic T stage and N stage was established, which showed better performance than the current TNM stage (P <0.05). Meantime, the new prediction model also applicable to papillary thyroid carcinoma and follicular thyroid carcinoma patients separately. Conclusions: This is the first study to question the rationality of current TNM stage for patients younger than 55 years and successfully develop a new prognostic model, which improve the prognostic stratification and guide individualized management.